Differential intervention effectiveness of a universal school-based resilience intervention in reducing adolescent substance use within student subgroups: exploratory assessment within a cluster-randomised controlled trial. Issue 8 (29th August 2018) - Hodder, Rebecca Kate; Freund, Megan; Bowman, Jenny; Wolfenden, Luke; Campbell, Elizabeth; Dray, Julia; Lecathelinais, Christophe; Oldmeadow, Christopher; Attia, John; Wiggers, John
Abstract : Objectives: Interventions addressing the individual and environmental protective factors of adolescents are suggested to have potential for reducing adolescent substance use. While universally delivered school-based substance use prevention interventions are common, previous studies have suggested variable effectiveness by subgroups of students. An exploratory study was undertaken to examine the differential effectiveness of a universal school-based resilience intervention on adolescent substance use and protective factors according to their sociodemographic and previous substance use. Design: Secondary analysis of data from a cluster-randomised controlled trial. Setting: 32 Australian secondary schools. Participants: Cohort of grade 7 students (n=3155) followed up in grade 10 (aged 15–16 years; 2014; n=2105). Intervention: Three-year universal school-based intervention implemented by school staff that targeted a range of student resilience protective factors (2012–2014). Measurements: Primary outcomes included: tobacco (recent, number of cigarettes) and alcohol (recent, 'risk' and number of drinks) use, and secondary outcomes included: marijuana (recent) and other illicit substance (recent) use, and aggregate individual and environmental protective factor scores. Generalised and linear mixed models examined interactions between treatment and student subgroups (gender; socioeconomic disadvantage (low/high); geographic location (major city/inner regional/outer regional-remote); and previous substance use (non-user/user)) at follow-up (36 models). Results: Analysis of student follow-up data showed no differential intervention effect for any substance use or protective factor outcome for any subgroup, with the exception of one differential effect found by socioeconomic status for the outcome of mean number of cigarettes smoked by recent smokers (p=0.003). There was no evidence of an intervention effect within the low (mean difference (MD) −12.89, 95% CI −26.00 to 0.23) or high (MD 16.36, 95% CI −1.03 to 33.76) socioeconomic subgroups. Conclusions: No evidence of an intervention effect on substance use and protective factors was found according to student subgroups defined by sociodemographic characteristics or previous substance use. Trial registration number: ACTRN12611000606987.